Kesantunan imperatif dalam interaksi santri putra pada madrasah aliyah kelas X Mu’allimin Muhammadiyah Yogyakarta - Abdurrahman, Wahid (LingTera, 2017)
Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan wujud kesantunan imperatif dalam interaksi dan mendeskripsikan makna kalimat imperatif yang digunakan dalam interaksi santri putra Madrasah Aliyah kelas X Mu’allimin Muhammadiyah Yogyakarta. Objek penelitian ini adalah kalimat imperatif lisan dalam bahasa Indonesia dan bahasa Jawa yang di dalamnya terkandung makna atau maksud pragmatik imperatif yang dituturkan oleh para guru, siswa dan pembina asrama pada waktu proses kegiatan/aktivitas. Metode yang digunakan dalam penelitian ini adalah metode simak dan cakap, teknik yang digunakan adalah simak libat cakap. Instrumen yang digunakan dalam penelitian ini adalah human instrument yaitu peneliti dilengkapi dengan alat rekam dan kartu data. Analisis data dilakukan dengan menggunakan metode kontekstual, yaitu cara analisis yang diterapkan pada data dengan mengaitkan konteks ujaran. Hasil penelitian ini diketahui bahwa delapan jenis makna imperatif pragmatik interaksi santri putra Madrasah Aliyah kelas X Mu’allimin Muhammadiyah Yogyakarta dilihat dari tingkat ilmu, bisa dikelompokkan menjadi (1) imperatif pragmatik yang mengandung makna dasar "perintah", yaitu makna desakan, bujukan, larangan, perintah, dan "ngelulu", (2) imperatif pragmatik yang mengandung makna dasar "permintaan", yaitu makna permintaan, dan (3) imperatif pragmatik yang mengandung makna dasar "nasehat ", yaitu makna himbauan dan persilaan. Imperative Politeness in Inter-Male Student Interaction of Class X Madrasah Aliyah Mu’allimin Muhammadiyah Yogyakarta Abstract This research has two purposes. First, to describe and explain the forms of imperative politeness in inter-male student interaction of Class X Madrasah Aliyah of Mu’allimin Muhammadiyah Yogyakarta. Second, to describe imperative sentences used in inter-male student interaction of Class X Madrasah Aliyah of Mu’alliminMuhammadiyah Yogyakarta. The object of this study includes all verbal utterances in Bahasa Indonesia which contain imperative pragmatic meanings or intentions uttered by the teachers, students, and dormitory managers of Madrasah Aliyah class X of Mu’allimin Muhammadiyah Yogyakarta during the process of activities. The data of this research comprise verbal utterances used by teachers, students, and dormitory managers of Madrasah Aliyah class X of Mu’allimin Muhammadiyah Yogyakarta which contain imperative pragmatic meanings or intentions in Bahasa Indonesia and Javanese. This study uses the observation and interviewing method, with observation, involvement, and interviewing technique. Human instrument used in this study was supported by recording device and data card. Data analysis was conducted using contextual method, which is applied to the data by basing on, taking into account, and associating with contexts. The results of the research show that eight types of pragmatic imperative meanings in the inter-male student interaction of Madrasah Aliyah class X of Mu’allimin Muhammadiyah Yogyakarta as seen from educational and institutional levels can be categorized into (1) pragmatic imperative containing the basic meaning of "order", i.e. insistence, persuasion, prohibition, order, and sarcasm (Javanese: ngelulu); (2) pragmatic imperative containing the basic meaning of "request", i.e. request; and (3) pragmatic imperative containing the basic meaning of "advice", i.e. urge and invitation.